A novel optimization method considering fluid production rate and division time for 2D reservoir. (November 2019) - Ma, Yinfei; Shi, Anfeng; Wang, Xiaohong; Tan, Baoguo; Sun, Hongxia
Abstract: The adjustment and control of the fluid production rates is one of the primary methods to increase the cumulative oil production for water flooding reservoir. In this article, the oil production optimization problem of two-dimensional water-flooding reservoir under the condition of fixed total fluid production rate is studied. The production process is divided into several segments. The relevance between the division time and the fluid production rate is considered. A novel optimization method considering both segmented time and fluid production rate is proposed. The stimulating effect on oil production of this method is tested by a realistic 2 dimensional oil reservoir in China. Compared with other conventional strategies and optimization schemes, this optimization method gains higher cumulative oil production, with the better water sweeping efficiency. For engineering practice, the proposed method may bring more economic benefits.